2003
DOI: 10.1159/000070653
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Connexin 32 Gene Expression through DNA Methylation in a Human Renal Cell Carcinoma Cell

Abstract: Background: We have recently reported that connexin (Cx) 32 is down-regulated in a human renal cell carcinoma (RCC) cell (Caki-2 cell). Hypothesis: We postulated that the down-regulation of Cx32 gene in the RCC cell is due to hypermethylation of its promoter region. Methods: We estimated methylation status in the promoter region of Cx32 gene in the RCC cell by DNA digestion with methylation-sensitive restriction enzyme and PCR, and methylation-specific PCR (MSP). We also checked the recovery of Cx32 gene expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 13 publications
1
28
0
Order By: Relevance
“…13 Hypermethylation in the promoter region is a mechanism for the Cx32 gene repression in human renal cell carcinoma cells. 22,23 Cx26 is a structural component of gap junctions expressed in breast epithelial cells. Expression levels of Cx26 are reduced in many breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…13 Hypermethylation in the promoter region is a mechanism for the Cx32 gene repression in human renal cell carcinoma cells. 22,23 Cx26 is a structural component of gap junctions expressed in breast epithelial cells. Expression levels of Cx26 are reduced in many breast tumors.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our previous study, preneoplastic and neoplastic lesions such as endometrial hyperplasia and carcinoma showed obvious decreases in levels of Cx26 and Cx32 mRNA, and immunohistochemically aberrant localization . Recently, several studies demonstrated that hypermethylation in the promoter region was a mechanism for the Cx32 gene repression (Singal et al, 2000;Tan et al, 2002;Hirai et al, 2003), although it was not found in other tumors (Loncarek et al, 2003). However, little is known about the mechanism decreasing GJIC in the endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, inactivation of the Cx26, Cx32 and Cx43 genes by hypermethylation of their promoter regions has been demonstrated. [162][163][164][165] Epigenetic effect of toxicants has been well documented for hepatic Cx43, 33,139 and could occur in the testis. This epigenetic effect could also be operative, during critical male programming windows of testis development, and lead to transgenerational reproductive dysfunction.…”
Section: Effects Of Environmental Toxicants On Connexin 43 In the Devmentioning
confidence: 99%